The application of an amended FCA method on knowledge acquisition and representation for interpreting meteorological services - Liu, Yong; Li, Xueqing (Journal of ambient intelligence and humanized computing, 2020)
In the process of building an ontology-based knowledge base, developers need to transform the knowledge within the domain into a system conceptual framework that can be processed. This process is usually divided into two parts: knowledge acquisition and knowledge representation. If the way of acquiring knowledge is arbitrary, it is easy to form a concept that does not have consensus. When generating a conceptual hierarchy, it also needs to face the transformation of level confirmation and expression. Based on formal concept analysis (for knowledge acquisition) and description logic (for knowledge representation), this paper explores the use, problems and inconsistencies of these two aspects, and proposes an amended method. In addition, a method of exploring how to develop an unknown concept is proposed. This paper provides an ontology case based on the application amended method for the meteorological service field to solve the problem that the hidden knowledge in the meteorological service field is difficult to find and the concept processing is inaccurate, and the Formal Concept Analysis and implementation process of the meteorological service field are expounded. The method after the correction is to collect abstract and objective concept formation factors, and finally name the specific and subjective concepts. The formation of the concept of ontology is more in line with the cognitive development process.